2020
DOI: 10.3390/molecules25173897
|View full text |Cite
|
Sign up to set email alerts
|

Focusing on the Catalysts of the Pd- and Ni-Catalyzed Hirao Reactions

Abstract: The Hirao reaction involving the phosphinoylation or phosphonation of aryl halides by >P(O)H reagents is a P–C bond forming transformation belonging to the recently very hot topic of cross-couplings. The Pd- or Ni-catalyzed variations take place via the usual cycle including oxidative addition, ligand exchange, and reductive elimination. However, according to the literature, the nature of the transition metal catalysts is not unambiguous. In this feature article, the catalysts described for the Pd(OAc)2-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 79 publications
(142 reference statements)
0
8
0
Order By: Relevance
“…The major disadvantage of TM-catalysed Hirao coupling is the high-catalyst loading (often more than 5 mol%). 6,9 Although it seems that the low catalyst loading is detrimental to conversion to the desired product 3a (entries 7 and 8 in Table 1), to our delight, both high conversion and isolated yield were realized in Hirao coupling catalysed by precatalyst 1a (1 mol%) (Scheme 8). Moreover, the amount of di-p-tolylphosphine oxide employed in the reaction was raised to 1 mmol.…”
Section: Conducting Hirao Coupling With a Low Catalyst Loadingmentioning
confidence: 94%
See 1 more Smart Citation
“…The major disadvantage of TM-catalysed Hirao coupling is the high-catalyst loading (often more than 5 mol%). 6,9 Although it seems that the low catalyst loading is detrimental to conversion to the desired product 3a (entries 7 and 8 in Table 1), to our delight, both high conversion and isolated yield were realized in Hirao coupling catalysed by precatalyst 1a (1 mol%) (Scheme 8). Moreover, the amount of di-p-tolylphosphine oxide employed in the reaction was raised to 1 mmol.…”
Section: Conducting Hirao Coupling With a Low Catalyst Loadingmentioning
confidence: 94%
“…8 Furthermore, it seems that the use of 5 mol% or even more transition-metal catalyst is commonly practised in such reactions at elevated temperature using an extended reaction time. 6,9 The requirement for a large amount of transition-metal ( pre)catalyst is a major drawback of Hirao coupling. Consequently, it is important to develop effective and efficient precatalysts in such applications.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the reaction conditions, costs and safety concerns, it can be concluded that the application of Pd(OAc) 2 is favorable, but the use of NiCl 2 can also be a good alternative. Moreover, the C-P coupling reactions which apply Ni(II) salts in the absence of reductants have been investigated earlier, including theoretical calculations [109,110]. These latest developments of Hirao coupling mean a big step forward to "P-ligand-free" catalytic reactions, since there is no need for sensitive and expensive P-ligands.…”
Section: Phosphonylation By Hirao Reactionmentioning
confidence: 99%
“…It was found that 20% of CuBr was the most efficient catalyst precursor using with 2 equiv. of NEt 3 at 165 • C. In the next stage, efficient "ligand-free" nickel-catalyzed (e.g., NiCl2) syntheses were also elaborated by our group [14][15][16][17]. In these cases, surprisingly, Ni(II)→Ni(IV) oxidation happened instead of the Ni(0)→Ni(II) formation.…”
Section: Cu(i)-catalyzed Hirao Reactionmentioning
confidence: 99%